Penguatan Karakter Mandiri melalui Pembelajaran Berdiferensiasi dalam Materi Bangun Ruang pada Siswa Kelas VI SD Negeri Wonorejo Tahun Pelajaran 2023/2024 - Nuraeni, Dewi (Lembaga Yasin AlSys, 2024)
Based on the research results of Classroom Action which can be carried out on geometrical object in three-dimensional space Material by applying differentiated learning to class VI students at SD Negeri Wonorejo, Polokarto District, Sukoharjo Regency for the 2023/2024 academic year for two cycles, conclusion can be drawn, namely that the Application of Differentiated Learning can strengthen the Independent character in geometrical object in three dimensional space Material. for sixth grade students at Wonorejo State Elementary School for the 2023/2024 academic year. Strengthening independent character is proven by a significant increase in the pre-cycle and every cycle. In the pre-cycle, the achievement score for the independent character reflection indicator was 66,81%. Then in cycle I the achievement value of the reflection indicator was 75,26% or an increase of 8,45% and in cycle II the achievement value of the reflection indicator increased to 82,55% or an increase of 7,29%.